ADSORBSI ION Pb2+ MENGGUNAKAN ARANG AKTIF KULIT DURIAN DENGAN METODE KOLOM ADSORBSI - Nurhaeni Nurhaeni; Musafira Musafira; Agus Rahmatullah (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2017)
Research has conducted using of activated charcoal from durian skin as an adsorbent of ion Pb2+ on water. This study aims to determine the effect of high adsorbent activated charcoal of durian skin and influence of adsorbent elution time. The method used in this study is SSA. The research design is applied is an RAL, with an independent variable are high adsorbent and adsorbent elution time. In this research, the variation applied adsorbent is 13.5 cm high, 18 cm, 22.5 cm, and 27 cm and variations adsorbent of the elution time are first, second, third, fourth, fifth, and sixth hour. The results showed that activated charcoal of durian’s skin 27 cm has a higher adsorption with the variation of high adsorbent with high levels of ion Pb is 80.019% and for variations in elution time adsorbent obtained the use of the first hour is more effective , Activated charcoal durian skin can be used as an adsorbent decreased levels of Pb ion in the water until the sixth hour.Keywords: activated charcoal, adsorbent, durian skin, Pb2+.